Buyer-supplier commitment and competitive performance among small and medium enterprises in Southern Gauteng - Nwele, Uju Kingsley (Vaal University of Technology, 2020)
Economic growth, job creation and improved standard of living have resulted to focus mostly on small and medium enterprises (SMEs) across the world. Hence, establishing and maintaining relationships with partners across the supply chain has become a prerequisite for achieving long-term competitive benefits in the present business competitive environment. For this reason, buyer-supplier commitment is deemed an important long-term business relationship strategy towards achieving competitive performance. Although buyer-supplier commitments can serve as the basis for the development of relational standards, unbalanced commitments, on the other hand, may become a harbinger of opportunistic behaviours. This development is inimical to continued business relationship and its consequential benefits for the SMEs’ supply chain collaborators. Guided by the theoretical lens of the social exchange theory (SET), this study examines the influence of communication, product quality, flexibility, and buyer-supplier commitments on SMEs competitive performance in southern Gauteng. Using a convenience sampling technique, the study quantitatively analysed the 396 returned questionnaires. Data analysis was conducted using the statistical package for social sciences (SPSS) version 25.0 and AMOS 25.0 for the confirmatory factor analysis and the structural equation modelling (SEM) respectively. The SEM analysis helped to confirm the suitability of the model fit as well as the positive and significant relationships of the proposed hypotheses. The analysis revealed that communication, product quality and flexibility are important variables in predicting buyer-supplier commitment as they displayed positive association with buyer-supplier commitment and the latter is significant in a firm’s effort towards achieving competitive performance. The study recommends the anchoring of SMEs strategies on commitment inorder for partners to efficiently and effectively enjoy competitive benefits. This research contributes new knowledge to the body of literature by developing a research framework on SME’s business growth and competitive performance and offered recommendations based on the study, which if implemented, could improve the economy. The study also revealed a higher relationship among the baseline constructs (communication, product quality and flexibility) which have received little or no conceptualisation in literature.
M. Tech. (Department of Logistics Management, Faculty of Management Sciences), Vaal University of Technology.
Keywords: Communication; Product quality; Flexibility; Buyer-supplier commitment; SMEs’ competitive performance; Dissertations, Academic -- South Africa; Business logistics; Physical distribution of goods; Product quality; Business enterprises -- Gauteng (South Africa)